Assessing the Role of Money versus Interest Rate in Pakistan (The Pakistan Development Review, 2020)
We have empirically examined the role of monetary aggregate(s) vis-à-vis short-term interest rate as monetary policy instruments, and the impact of State Bank of Pakistan’s transformation into the latter on their relative effectiveness in terms of inflation in Pakistan. Using indicators of ‘persistent changes’ in the underlying behaviours of variables of interest, we found that broad money consistently explains inflation in (i) monetary (ii) transitory and (iii) interest rate regimes. Though its role has receded while moving from the transition to the interest rate regime, the interest rate instrument seems to be positively related to inflation, a phenomenon commonly known as price puzzle. In light of these findings, we recommend that the role of money should not be completely de-emphasised. JEL Classification: E31, E52. Keywords: Monetary Policy Instruments, Price Puzzle, ARDL, Pakistan